The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.brs.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and electrophysiological outcomes of deep TMS over the medial prefrontal and anterior cingulate cortices in OCD patients

Abstract: HF DTMS over the mPFC-ACC alleviates OCD symptoms and may be used as a novel therapeutic intervention. Notwithstanding alternative explanations, this may stem from DTMS ability to directly modify ACC activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(156 citation statements)
references
References 74 publications
3
144
0
2
Order By: Relevance
“…Resting-state fMRI can further be used to develop brain-based treatment frameworks targeting this common neural substrate. Furthermore, previous studies have investigated the feasibility of brain stimulation techniques targeting the SN, observing symptom improvement in different psychiatric disorders following the stimulation of the dACC (Carmi et al, 2018;Hayward et al, 2007;Kreuzer et al, 2015;Vanneste, Ost, Langguth, & Ridder, 2014). A common target site for therapeutic repetitive transcranial magnetic stimulation (rTMS) is the prefrontal cortex (Fitzgerald, Maller, Hoy, Thomson, & Daskalakis, 2009).…”
Section: Bnmentioning
confidence: 99%
“…Resting-state fMRI can further be used to develop brain-based treatment frameworks targeting this common neural substrate. Furthermore, previous studies have investigated the feasibility of brain stimulation techniques targeting the SN, observing symptom improvement in different psychiatric disorders following the stimulation of the dACC (Carmi et al, 2018;Hayward et al, 2007;Kreuzer et al, 2015;Vanneste, Ost, Langguth, & Ridder, 2014). A common target site for therapeutic repetitive transcranial magnetic stimulation (rTMS) is the prefrontal cortex (Fitzgerald, Maller, Hoy, Thomson, & Daskalakis, 2009).…”
Section: Bnmentioning
confidence: 99%
“…Because the interim analysis showed no difference between the sham and 1 Hz arms, the study was continued with just high frequency and sham. At the end of the study, the response rate in the 20 Hz arm was much greater than in the sham group and the improvements were still present a month after treatments ended [25,26].…”
Section: Detailed Review Of Sham-controlled Trials Using Tms For Treamentioning
confidence: 87%
“…Baseline symptom severity for inclusion was de ned as a score of 16 or higher on the Y-BOCS (Mean = 22.20, SD = 7.01), which is the cut-off criterion for moderate OCD (8-15 mild, 16-23 moderate, 24-31 severe, 32-40 extreme). Treatment response was de ned as a reduction of at least 30% in the Y-BOCS total score, based on some previous studies [32,46] and is suggested to represent a relevant clinical improvement (i.e., improvement of Clinical Global Impression (CGI)). Although 35% of symptom reduction is taken as "response" criterion in other studies [47], we chose a more liberal criterion to achieve a more balanced response distribution for the binary regression analysis.…”
Section: Clinical Proceduresmentioning
confidence: 99%
“…In this line, recent reviews of rTMS studies show that brain state-dependent modulatory effects of rTMS are an additional parameter that may potentially affect rTMS effects [29], and taking this factor into account might improve treatment outcomes in patients who usually develop treatment-resistant illness subtypes. Moreover, different cortical regions have been targeted in previous studies with mixed results [30][31][32][33][34], leaving the question of which cortical regions to stimulate unanswered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation